Analysis Comparison of PSMEID With Preview for Controlling Shock Vibration of UAV’s Landing Gear System - Darmawan; Lovelyson; Meifal Rusli; Rahmadi Kurnia; Amirul Luthfi (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2025)
Semi-active dampers reduce the effects of shock vibrations because they can operate at specific vibration frequencies at a lower cost than more complex active dampers. PSMEID is one of the alternative methods developed in the semi-active damping system. PSMEID has been developed by adapting it by adding a PSMEID active time prediction system when an impact occurs. This research attempts to compare two types of PSMEID with active time prediction, where the position of each model offered has a different PSMEID mass position when applied to the landing gear damper of an Unmanned Aerial Vehicle (UAV). This comparison aims to give the user a choice among these optimal models suitable for use in multiple conditions. When simulated using the same parameter values, the PSMEID placed on the unsprung mass can reduce acceleration amplitude by up to 6.6 percent when the landing gear is dropped at 0.15 meters from the ground. The model that places the PSMEID on the sprung mass can help reduce the velocity amplitude up to 8.8 percent when dropped at a height of 0.05 meters, and the spring constant value of the PSMEID (KPS) is 1600 N/m. All these simulations show that the PSMEID should be activated just before the landing gear hits the runway surface (TB < TL).